8 Hepatic Function Predicts Hospitalisation and All Cause Death in Patients with Heart Failure. (3rd June 2016) - Singh, Jagdeep; Levin, Daniel; Lang, Chim C
Abstract : Introduction: Hepatic dysfunction has always been considered as a sequel of chronic heart failure (CHF), however there has been recent interest in it being used as a marker of disease severity instead. Previous studies have demonstrated this among patients in clinical trial settings but no population based studies have been conducted thus far. We aim to determine the impact of hepatic dysfunction on a composite of all cause mortality and heart failure hospitalisation in patients treated for CHF. Methods: We analysed data from the Systems BIOlogy Study to Tailored Treatment in Chronic Heart Failure (BIOSTAT-CHF) database which prospectively tracks treatment, comorbidity, blood investigations, hospitalisation and death information of patients with heart failure from Tayside and Fife. Cox proportional hazard models were used to assess the prognostic impact of liver dysfunction on heart failure outcomes, while controlling for covariates like treatment regime, previous history of myocardial infarctions, atrial fibrillation, renal disease and CHF duration. Results: Out of a total 1805 patients, there were 1200 (66.5%) males, with a mean age of 73.6 (±10.7) years, and mean duration of HF 39.9 months with a total of 414 all cause death or heart failure hospitalisation. We found low serum albumin levels (less than 35 g/L) to be an independent predictor of CV death or hospitalisation with a hazard ratio of 2.05 (95% CI 1.51–2.79, p < 0.001). Similarly, elevated bilirubin (more than 20 µmol/L) and alanine aminotransaminase (ALT) (more than 35 U/L) increased the risk of outcomes with hazards of 1.97 (95% CI 1.56–2.50, p < 0.001) and 1.31 (95% CI 1.04–1.66, p = 0.024) respectively. Conclusions: Our findings demonstrate lower serum albumin, elevated total bilirubin and ALT were independent predictors of all cause death or hospitalisation among an unselected group of HF patients. These markers can be easily used to risk stratify ambulatory CHF patients in the clinic.